WARUNG KOPI DAN SIMBOLISASI KEISLAMAN (Studi Kasus Di Kota Yogyakarta) - Rohimi (UIN Mataram, 2022)
Coffee is one of the plantation products that have such a culminative income. coffee is someone's favorite drink in almost every country including the Indonesian people, for example in Makassar, Jakarta, Surabaya, Bandung and the city of Yogyakarta. This study aims to analyze how the existence of coffee, coffee shops and the symbolization of Islamic values ??in the city of Yogyakarta. This research is a field research conducted in several coffee shops in the city of Yogyakarta, with data collection methods namely interviews, observation and documentation. Sources of data used in this study are primary sources from field results and secondary sources assisted by literature review or research that is relevant to the discussion theme raised by the researcher in this study. The results and discussion in this study that the purpose or perspective of Islamic symbols in this coffee shop can be concluded by researchers like. First, to increase the religious value of the visitors who visit the coffee shop. Second, to continue to carry out worship for coffee connoisseurs, so that they are not only concerned with the world or their pleasures when facing a coffee shop (aesthetic). Symbols of Islamic values ??in coffee shops in the city of Yogyakarta also include places of worship (mushola), writing Islamic nuances as a form of enhancing the spirituality of visitors in coffee shops, and creating discussion agendas with the theme of religious values.